COMPARATIVE CONTEXT IN THE ONLINE TEXT OF TELAGA WARNA DIENG LEGEND - Hanova Rani Eka Retnaningtyas (Acceleration: Multidisciplinary Research Journal, 2023)
This research is a qualitative descriptive study that utilizes the method of comparison to analyze the data. The basic technique used is the technique of determining elements (PUP), and the advanced technique used to assist data analysis is the technique of distinguishing comparative relationships (HBB). The overall methods and techniques are used to compare and contrast the contexts found in three stories about the legend of Telaga Warna Dieng in Wonosobo Regency, Central Java, Indonesia. The stories compared are derived from three online texts found on three blog sites, namely Legenda Dieng, Kelasindonesia.com, and Wonosobo Asri. The issue addressed in this research is the differences found in the three online texts. This is intended as an initial step in understanding the local wisdom embodied in the legend of Telaga Warna Dieng, so that there will be no misunderstandings in understanding each version of the story that emerges. The results of this research indicate that there are differences in the stories among the three online texts examined. The differences that arise are in the context based on personal interpretation, locational interpretation, and temporal interpretation.